The Wife’s Rights After Divorce in Islamic law: A Comparative Study - Samia Abdel Basset El Sheikh (International Journal of Law Research and Studies, 2024)
Islamic law has paid special attention to women’s rights, given their important role in the family and society, and has also guaranteed men’s rights. Therefore, each party must know their duties and rights towards the other, and the ways to achieve satisfaction for both parties. Disagreements may arise between spouses as a result of failure to perform duties, which may lead to divorce. When divorce occurs, rights are established that protect both parties from harm. This study focuses on presenting the wife’s rights after divorce, such as dowry, alimony, housing, the right to breastfeeding wages, and the right to custody of children. It also presents how these rights are addressed in the Arab Republic of Egypt, the Kingdom of Saudi Arabia, and Morocco.